Development of Fiqih-Based Learning Devices Problem Based Learnig (Pbl) With Artificial Intelligence Improves Skills Critical Thinking of Madrasah Aliyah Students - Fadriati; T Idris; Yoprisya; Rahimatul Yusra; Yolanda Afrilia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The problem with this research is that educators do not understand the discussion that will be conveyed to students, so a guidebook for fiqh learning tools based on problem-based learning with artificial intelligence was created. So that students can understand what the teacher conveys in the classroom learning process. This research aims to find out how the validity and practicality of media in the form of Problem Based Learning (Pbl) Fiqh Learning Tools with Artificial Intelligence Improve the Critical Thinking Skills of Madrasah Aliyah Students. This research uses research and development (R&D) methods, using the 4D development model. The research and development procedure consists of 4 stages, namely: 4D Model (define, design, develop, and disseminate). Conduct trials and find out the practicality of learning videos on Zakat material in Fiqh subjects. The instruments used in this research and development are questionnaires in the form of validation sheets, teacher and student response questionnaires. Data analysis techniques to determine research results are validity analysis and practicality analysis.